Consumer preferences towards healthier reformulation of a range of processed meat products: A qualitative exploratory study. Issue 9 (4th September 2017) - Shan, Liran Christine; Regan, Áine; Monahan, Frank J.; Li, Chenguang; Lalor, Fiona; Murrin, Celine; Wall, Patrick G.; McConnon, Áine
Abstract : Purpose: In response to increasing public health concerns about processed meat consumption, many innovations in meat technology focus on health-oriented product reformulations. Processed meat is not a homogeneous food category. The purpose of this paper is to explore consumer perception of the "healthier" reformulation of different processed meat products using two approaches: salt and fat reduction; and enrichment with healthy ingredients. Design/methodology/approach: Seven focus group interviews were carried out with 40 Irish regular meat consumers (30 female, ten male) who were solely or jointly responsible for food shopping. Two rounds of card sorting procedures were employed to reveal perceptions on reformulation of 20 different processed meat products. Thematic analysis was used for analysing transcripts. Findings: Health and flavour concerns and product popularity were the main factors influencing participants' perceptions. Some participants were unsure or had misconceptions about the healthiness of certain meat products. Participants suggested reducing salt and fat content in processed meat products they perceived as the least healthy ones (theme 1) and improving the healthiness of products which were favoured by children (theme 2) and those meat products which people consumed regularly as a source of protein (theme 3). Participants were not in favour of any reformulation of speciality-type products (theme 4). Originality/value: Consumer insights identified in this study can inform future approaches to making processed meats healthier.